FOOD SAFETY OF GENETICALLY MODIFIED ORGANISM ACCORDING TO INTERNATIONAL LAW AND ITS IMPLEMENTATION IN INDONESIA - Risa Mahdewi; Desia Rakhma Banjarani (Lampung Journal of International Law, 2020)
Modern biotechnology products have provided considerable benefits for improving human life and well-being, both in the agriculture, food, industry and human health sectors, as well as in the environmental field. But there are concerns that modern biotechnology products, in addition to providing benefits, also have risks that have adverse impacts on the conservation and sustainable use of biodiversity and human health. Therefore, steps need to be taken, both legally, administratively, and technology to ensure the level of biological safety. This study aims to explain and analyze the safety of Genetically Modified Organism or GMO according to international law and their implementation in Indonesia. The problem approach used in this research is normative law (library research). The data used are secondary data obtained from international, national legal regulations and literature data related to material that supports discussion of the problem. Analysis of the data used is descriptive qualitative. The results of research on food safety of Genetically Modified Organism or GMO according to international law, are regulations on food safety of genetically engineered products regulated in the Convention on Biological Diversity and the Cartagena Protocol on Biosafety. The laws and regulations governing GMO food in Indonesia are good enough because they have carried out the mandate and did not deviate from the biodiversity convention and Cartagena protocol by passing legislation regulations from the legal level to the decision level of the head of BPOM. It’s just that for rules regarding GMO food that is sold in retail, or that is not in the form of packaging, there is still no technical rules that can answer the problems in the field.